Spirometry assessment of interstitial lung disease patients and correlation with its clinical and radiological profile - Balas, Zeel C.; Jotkar, Sushama (International Journal of Research in Medical Sciences, 2022)
Background: Interstitial lung diseases (ILD) are a diverse set of lower respiratory tract illnesses that are defined by both abrupt and persistent inflammation as well as a largely irreversible and continuous progression of fibrosis in the interstitium and the walls of the alveoli. This study focuses on non-invasive techniques for clinically and radiographically confirmed situations. Since most patients refuse surgical or transbronchial lung biopsies and are in respiratory difficulty, an alternate method is preferable. Spirometry tests are often used as diagnostic aids. This study compares spirometry in ILD patients with their radiological and clinical features. Methods: In this prospective observational study, 50 ILD patients who were diagnosed on the clinical and radiological grounds included. A detailed history of illness was obtained and noted. All patients were examined clinically and underwent basic investigations. All patients were performed 6 MWT O2 saturation and spirometry. Correlation between spirometry findings and clinical and radiological profile was done. Results: The study group of 50 patients with ILD, idiopathic pulmonary fibrosis was the most common cause of ILD consists of 32 patients performing 64% of the study group. Average duration of symptoms in ILD patients in this study was 5.46±5.49 months. The mean age of the patients was 61.58±12.92 years ranging from 27 to 88 years with 27 (54%) male and 23 (46%) female. Cough and dyspnoea were the most common features at presentation in our study group, present in almost all the patients. Crepitations were present in 41 (82%) patients. Most common chest X-ray feature was reticular opacities which was present in 24 (48%) patients. Ground glass opacity in high-resolution computed tomography (HRCT) was seen in 33 (66%) patients. Most common spirometry pattern seen in our study was Restrictive pattern which was present in 42 patients. In ILD patients, mean values of FEV1% was 59.2±20.33, FVC% was 60.76±25.45, FEV1/FVC was 100.86±20.12. Conclusions: Idiopathic pulmonary fibrosis is the most common and chronic hypersensitivity pneumonitis along with cryptogenic organizing pneumonia are the second common ILD in our study. The underdiagnosis of interstitial lung disease is due to a lack of knowledge among doctors. Therefore, spirometry and 6MWT O2 saturation should be performed in all patients presented with complaints of chronic cough and breathlessness as screening tool and then HRCT chest and biopsy can be done for confirmation of diagnosis. So early diagnosis and treatment of ILD patients is possible with use of spirometry.